Assessment of job satisfaction among resident doctors in a public healthcare facility in Enugu state Southeast Nigeria - Ogugua, Ifeoma J.; Kassy, Chukwukasi W.; Ochie, Casmir N.; Nwoga, Hope O.; Achigbu, Kingsley I.; Chukwumam, Denning; Aguwa, Emmanuel N.; Aniwada, Elias C.; Okwor, Tochi J. (International Journal Of Community Medicine And Public Health, 2022)
Background: The effect of job satisfaction on work quality, work efficiency, and health care costs is known to be particularly significant in the healthcare sector. With the current brain drain crisis in the Nigerian health system, attention must be paid to doctors’ job satisfaction for improved quality health care and patient safety. This study assessed the level of job satisfaction and associated factors among resident doctors working at the University of Nigeria Teaching Hospital, Enugu Nigeria. Methods: This facility-based cross-sectional study was conducted among 255 resident doctors using a validated 10-item Warr-Cook-Wall job satisfaction scale. A convenience sampling technique was employed and data were analyzed using Statistical package for social sciences (SPSS) version 21 software. The Chi-square test was used to determine the association between socio-demographic variables and overall job satisfaction. The level of statistical significance was determined by a p<0.05. Results: The majority of the respondents (62.7%) were not satisfied with their job in general. There were statistically significant association between the respondent’s salary (p=0.028), area of specialization (p<0.001), and years in residency training (p=0.007) and job satisfaction. The majority of the respondents were dissatisfied with physical working conditions (75.7%), hours worked (72.5), recognition for work (66.7%) and opportunities to use abilities (63.9). Conclusions: The overall level of job satisfaction among resident doctors was low. It is, therefore, important for the hospital managers to set up policies to tackle the factors identified for improved job satisfaction.